2006
DOI: 10.1097/00004836-200608000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Carcinoids: The Evolution of Diagnostic Strategies

Abstract: Carcinoid tumors are rare, often insidious neoplasms arising from neuroendocrine cells. The majority arise in the gastrointestinal system, and are often incidentally found during investigation, although some may present as an emergency bleed or perforation. The prosaic symptoms of flushing, diarrhea, and sweating are often overlooked; thus, the diagnosis is usually much delayed and the tumor is advanced at presentation. This diagnostic delay renders effective management difficult and adversely affects outcome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
12

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 96 publications
0
64
0
12
Order By: Relevance
“…Second, carcinoid tumors are mostly asymptomatic but can sometimes cause small bowel obstruction and rarely, bleeding too. Third, CT and MRI may be used for initial localization of the tumor only because both imaging techniques may miss lesions otherwise detected by 111In-octreotide scintigraphy; one study has shown that lesions in 50% of patients were missed, especially in lymph nodes and extrahepatic locations [6,7]. Last but not the least, prognosis can be markedly improved by early diagnosis and surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…Second, carcinoid tumors are mostly asymptomatic but can sometimes cause small bowel obstruction and rarely, bleeding too. Third, CT and MRI may be used for initial localization of the tumor only because both imaging techniques may miss lesions otherwise detected by 111In-octreotide scintigraphy; one study has shown that lesions in 50% of patients were missed, especially in lymph nodes and extrahepatic locations [6,7]. Last but not the least, prognosis can be markedly improved by early diagnosis and surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…6 Overall sensitivity of the octreotide scan is reported to be as high as 90%; however, false negatives (ie, failed detection) may result from various technical issues including small tumor size, or from inadequate expression of somatostatin receptors. 7 CT and magnetic resonance imaging (MRI) are important modalities used in the localization of carcinoid primaries and/or metastases. The median detection rate and sensitivity of CT and/or MRI have been estimated at 80%; detection rates by CT alone vary from 76% to 100%, whereas MRI detection rates vary from 67% to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread endoscopic screening, increased awareness of neuroendocrine histology, and improved data capture likely have contributed to this trend [4,5,[9][10][11]. The most common primary site of colonic NENs is the cecum, followed by sigmoid colon and ascending colon.…”
Section: Gastroenterology Research and Practicementioning
confidence: 99%